Intermittent Visual Occlusions Increase Balance Training Effectiveness - Symeonidou, Evangelia-Regkina; Ferris, Daniel P. (Frontiers in Human Neuroscience, 2022)
Improving dynamic balance can prevent falls in humans with neurological and mechanical deficits. Dynamic balance requires the neural integration of multisensory information to constantly assess the state of body mechanics. Prior research found that intermittent visual rotations improved balance training during walking on a narrow beam, but limitations from the immersive virtual reality headset hindered balance training effectiveness overall. We theorized that intermittent visual occlusions with electrically controlled liquid crystal glasses would overcome the previous limitations of the immersive virtual reality headset and provide a means to enhance dynamic balance training efficacy. Forty healthy young individuals walked on a treadmill-mounted balance beam for 30 min (20 subjects with intermittent visual occlusions and 20 subjects with unperturbed vision). Balance performance, in number of step-offs of the beam, improved by 78% for the visual occlusions group on the same day of the training, a near fourfold improvement compared to the 21% improvement for the unperturbed vision group (t(38) = –5.2, p < 0.001). The difference between groups was also apparent 2 weeks later testing for retention (60% improvement for the visual occlusions group, 5% for the unperturbed vision group; t(38) = –4.2, p < 0.001). Intermittent visual occlusions are likely a simple method for enhancing balance training in dynamic motor tasks.